Safety Analysis of the Grounding System at the 150 kV Simpang Haru Substation Using the Grid Grounding System Method Based on the IEEE Std 80 Standard - Danil Danil; Hamdani Hamdani; Siti Anisah (Sean Institute, 2026)
The grounding system at the substation is an important part of the electric power system that functions to maintain the safety of humans and equipment against ground fault currents. A grounding system that does not meet standards can cause touch voltages and step voltages that are dangerous for personnel and electrical equipment. This study aims to analyze the safety of the grounding system at the 150 kV Simpang Haru Substation using the Grid Grounding System method based on the SPLN and IEEE Std 80 standards. The analysis was carried out by calculating the grounding grid resistance value, Ground Potential Rise (GPR), touch voltage, and step voltage. The research data were obtained from the technical data of the substation grounding system including soil resistivity, grounding grid area, conductor length, and single-phase ground fault current. The results showed that the grounding resistance value of 0.49 Ω still meets the SPLN standard, which is below 1 Ω. The Ground Potential Rise value obtained was 5.88 kV. The touch voltage of 96 Volts and the step voltage of 36 Volts are still below the IEEE Std 80 safety limits of 638 Volts and 2,204 Volts, respectively. Based on the results of the analysis, the grounding system at the Simpang Haru 150 kV Substation is declared safe and meets safety standards based on SPLN and IEEE Std 80.